2023
DOI: 10.1111/jrh.12755
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of critical access hospitals and other rural acute care hospitals in Pennsylvania

Abstract: PurposeAs the Flex Program celebrates its 25th anniversary, we examined changes in critical access hospital (CAH) financial performance, investigated whether CAH status has reduced hospitals’ financial vulnerability, and identified factors influencing financial performance.MethodsWe collected data on acute care hospitals in Pennsylvania's rural counties for 2000‐20. Our sample contained 1,444 hospital‐year observations. We used trend analysis to compare the financial performance of CAHs and rural prospective p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…These challenges were accompanied by multiple Critical Access Hospital (CAH) closures. The North Carolina Rural Health Research Program's (NC RHRP), real-time tracking reported 80 closures (Cai et al, 2017). To add to the problem, about an additional 673 rural hospitals were vulnerable to closure, with 68% of those being CAHs (Cai et al, 2017), leading up to the arrival of the 2019 COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These challenges were accompanied by multiple Critical Access Hospital (CAH) closures. The North Carolina Rural Health Research Program's (NC RHRP), real-time tracking reported 80 closures (Cai et al, 2017). To add to the problem, about an additional 673 rural hospitals were vulnerable to closure, with 68% of those being CAHs (Cai et al, 2017), leading up to the arrival of the 2019 COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The North Carolina Rural Health Research Program's (NC RHRP), real-time tracking reported 80 closures (Cai et al, 2017). To add to the problem, about an additional 673 rural hospitals were vulnerable to closure, with 68% of those being CAHs (Cai et al, 2017), leading up to the arrival of the 2019 COVID-19 pandemic. Furthermore, new demands from Affordable Care Act (ACA) (Patient Protection & Affordable Care Act, 2010) were posing new demands on rural health clinics' resources (Haddox, 2018).…”
Section: Introductionmentioning
confidence: 99%